2014
DOI: 10.4028/www.scientific.net/amr.925.323
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic Behavior of Spiropyrans: The Effect of Substituent

Abstract: Spiropyrans are among the most promising organic photochromic dyes. However, spiropyrans are very sensitive dyes and there are many independent factors that can affect the performance of these dyes. The effect of substituent on the optical absorption spectra, fading kinetic, and also the dye stability of spiropyrans in diphenyl ether by UV irradiation has been investigated. The 6-nitro BIPS displayed greater absorbance intensity of 0.740% at 600nm compared to 8-ethoxy-6-nitro BIPS of 0.651% at 620nm. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Despite much work in this field, a comparative study between spiropyrans, spiroindolinonaphthopyrans, and spirooxazines with the same substituent patterns has not been conducted (Figure ). Previous literature reports have demonstrated that electron-withdrawing groups on the chromene ring enhance the UV response of photoswitches . However, little work has been done to understand how these groups affect the visible light response of photochromic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Despite much work in this field, a comparative study between spiropyrans, spiroindolinonaphthopyrans, and spirooxazines with the same substituent patterns has not been conducted (Figure ). Previous literature reports have demonstrated that electron-withdrawing groups on the chromene ring enhance the UV response of photoswitches . However, little work has been done to understand how these groups affect the visible light response of photochromic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…RSM is more cost-effective than OFAT due to the factors displayed in the table below (Table 1). 188 Commonly, Minitab and Design Expert provide RSM service for the optimization process. The steps for conducting RSM include experimental design, response model development, analysis of variance, optimization, and validation.…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…The presence of an axial point in the central composite design allows the extreme combination of design space while the Box-Behnken design provides the design in a safe operating zone only due to the absence of an axial point. After selecting Table 1 Summary of comparison between RSM and one-factor-at-a-time method 188…”
Section: Response Surface Methodology (Rsm)mentioning
confidence: 99%
“…The absorbance and fading kinetic measurements were performed according to the method described by Nadir et al [17,18]. The dyes were irradiated with UV lamp (Efos Acticure A4000) at an intensity of 0.5 mW/cm 2 .…”
Section: Characterizationsmentioning
confidence: 99%
“…SpectraSuite software was employed to measure the absorption spectra and fading kinetic as it can control the Ocean Optics USB spectrometer and support a real-time measurement [18]. Meanwhile, the design of experiments was planned and analysed using the statistical software package Minitab® 16.2.0.…”
Section: Softwarementioning
confidence: 99%